Kualitas Pembangunan Manusia Di Wilayah Koridor Ekonomi Papua-Kepulauan Maluku - Febrianti, Fitri; Nuraini, Ida (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
Currently, human development in Indonesia is still uneven, especially between western Indonesia and eastern Indonesia. The purpose of this study was to analyze the effect of per capita expenditure, the gini ratio, and the open unemployment rate on the human development index in the Papua-Maluku Islands economic corridor which is the eastern part of Indonesia. The type of data in this study is secondary data. The data source is the Indonesian Statistics Center for 2014-2020. The analysis used is multiple regression with panel data. The results of the study reveal that per capita expenditure has a positive and significant effect on the human development index, the gini ratio has a negative and insignificant effect on the human development index, while the open unemployment rate has a negative and significant effect on the human development index in the Papua-Maluku Islands economic corridor.